Eutrofização e qualidade da água na piscicultura: consequências e recomendações - Macedo, Carla Fernandes; Sipauba-Tavares, Lucia H. [UNESP] (Inst Pesca, 2010)
The eutrophication (cultural or anthropogenic) is induced by man and can have different origins, such as domestic sewage, industrial and agricultural activities, including the effluent still breeding systems of aquatic organisms. The expansion of aquaculture, with production of biomass and increase of nutrients in water may cause acceleration of productivity of algae, changing the ecology of aquatic systems. In addition, these waste water may present a risk to health through the transfer of pathogens from manure, plant residues, composted material, among others that are major sources of organic waste in some farming systems. Depending on the trophic level of fish ponds, which are dynamic environments, different planktonic species with short reproductive cycle and adapted to the changes contained in these systems can appear in high abundance. Water quality in the systems for raising fish is related to several factors, such as water source, management (liming, fertilizing, cleaning), cultivated species and quantity and composition of exogenous food. In order to minimize environmental impacts, there are techniques to improve the quality of water in fish farming systems and thus satisfactory answers can be obtained through the application of management practices. This paper aims to review the subject that deals with changes in water quality resulting from the activity of freshwater fish culture in Brazil. Search also recommend techniques of good management practices to minimize the impact generated by the activity.
Eutrophication and water quality in pisciculture: consequences and recommendations
Keywords: Best management practices; nutrients; fish pond; effluents treatment